Impact of the global economic crisis on the Thai automotive industry : from the perspective of the interplay between shocks and the industrial structure - Haraguchi, Nobuya (UNIDO ViennaAT, 2010)
Introduces the background of the Thai automotive industry, with facts and figures provided to illustrate the transmission and unfolding of the current crisis in the industry. Discusses the evolution of the industrial structure and their interplay with past crises. Focuses on the transmission mechanism and effects of the crisis and elucidates their similarities and differences in comparison with past crises.